Syntactico-semantic analysis of Agency and Action in Selected Excerpts from Obama's Speech to the 66th UNGA - Sultan, Mousa S.; Abdulrahman, Lamees, A. (International Journal of Linguistics and Translation Studies, 2022)
This paper traces the representation of Yemen and Syria in President Obama’s speech addressed to the 66th session of the UN General Assembly. In particular, the paper focuses on the syntactic selection of agency choices Obama used to ideologically represent the Yemeni and Syrian revolutions and their supporters. We investigate how Obama’s speech communicated ideologically interested messages which position the USA vis-à-vis the two revolutions and the people therein. The study arrived at the conclusion that Obama’s choices tended to either directly or indirectly represent the two countries and their people in positive light. It was observed that the opponents of the two revolutions were primarily, though indirectly, represented in negative light. We also found out that Obama’s use of highly evocative language tended to ideologically position the USA in positive light and as the voice of the voiceless and of the underprivileged. This in turn revealed the USA indirect support and recognition of the legitimacy of the revolutions and revolutionaries in the two countries. The study furthermore shows that language can be a very powerful tool for expressing ideologically interested positions, hegemonic control, as well as manufacturing consent with the target audience.